2007
DOI: 10.1097/01.mej.0000228447.48276.7b
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis: a challenging diagnosis

Abstract: The objective of the study was to evaluate our recent experience in diagnosis and management of necrotizing fasciitis. Records of patients who were diagnosed as having necrotizing fasciitis at Al-Ain Hospital in the period between March 2003 and August 2005 were studied retrospectively with regard to clinical features, risk factors, diagnosis, causative organisms, treatment, and outcome. Eleven patients, eight of whom were men of low socio-economic status, were studied. The median age (range) was 46 (8-65) yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
(22 reference statements)
1
34
1
1
Order By: Relevance
“…(12) reported A. baumannii as a monomicrobial cause of necrotizing fasciitis in 2 of 87 cases. However, the same study found a single pathogen as the causative agent of necrotizing fasciitis in 67.8% of the cases studied, a finding that is inconsistent with those of most other studies, which have reported a polymicrobial cause in the majority of cases (6,8,10,11,19). Liu et al acknowledged that their high rate of monomicrobial isolation might have been due to "relatively unsophisticated techniques for collection, transfer, or culture of anaerobic specimens," but they did not explain this further (12).…”
Section: Not Performed յ2mentioning
confidence: 68%
See 1 more Smart Citation
“…(12) reported A. baumannii as a monomicrobial cause of necrotizing fasciitis in 2 of 87 cases. However, the same study found a single pathogen as the causative agent of necrotizing fasciitis in 67.8% of the cases studied, a finding that is inconsistent with those of most other studies, which have reported a polymicrobial cause in the majority of cases (6,8,10,11,19). Liu et al acknowledged that their high rate of monomicrobial isolation might have been due to "relatively unsophisticated techniques for collection, transfer, or culture of anaerobic specimens," but they did not explain this further (12).…”
Section: Not Performed յ2mentioning
confidence: 68%
“…Most studies find necrotizing fasciitis to be polymicrobial in approximately 70% of cases, with the most common microorganisms identified as being group A and B streptococci, the staphylococci, members of the family Enterobacteriaceae, and Pseudomonas aeruginosa (6,8,10,11,19). Necrotizing fasciitis is therefore, no longer known as "acute streptococcal gangrene," the term originally used to describe the syndrome by Meleney in 1924 (14).…”
Section: Not Performed յ2mentioning
confidence: 99%
“…The disease progresses faster in patients with diabetes, chronic kidney insuf iciency, immunocompromising diseases, patients with surgical traumas and patients undergoing radiation therapy. The diagnosis is based on clinical signs that initially can be hard to notice, that's why the diagnosis is set in the late stages of the disease, which results in comparatively high mortality [7][8][9][10][11]. In this case one of the major factors that had a role in the spreading of the infection was the infected cyst that was treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…2 This condition is a significant surgical emergency; the diagnosis is often elusive in the early stages and should be considered in all cases of severe cellulitis, especially those resistant to antimicrobial agents. 3,4 The delay resulting from the diagnostic challenge of necrotizing fasciitis inevitably leads to increased mortality. 5 Implantation of a PPM is the treatment of choice for bradyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%